Regulatory T-Cells as an Emerging Barrier to Immune Checkpoint Inhibition in Lung Cancer - Principe, Daniel R.; Chiec, Lauren; Mohindra, Nisha A.; Munshi, Hidayatullah G. (Frontiers in Oncology, 2021)
Immune checkpoint inhibitors (ICIs) have revolutionized the treatment paradigm for lung cancer in recent years. These strategies consist of neutralizing antibodies against negative regulators of immune function, most notably cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), programmed cell death protein 1 (PD-1), and PD-1 ligand 1 (PD-L1), thereby impeding the ability of tumor cells to escape immune surveillance. Though ICIs have proven a significant advance in lung cancer therapy, overall survival rates remain low, and lung cancer continues to be the leading cause of cancer-related death in the United States. It is therefore imperative to better understand the barriers to the efficacy of ICIs, particularly additional mechanisms of immunosuppression within the lung cancer microenvironment. Recent evidence suggests that regulatory T-lymphocytes (Tregs) serve as a central mediator of immune function in lung cancer, suppressing sterilizing immunity and contributing to the clinical failure of ICIs. Here, we provide a comprehensive summary of the roles of Tregs in lung cancer pathobiology and therapy, as well as the potential means through which these immunosuppressive mechanisms can be overcome.